2020
DOI: 10.1038/s42003-020-0786-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual bias is reduced with longer reaction times during visual discrimination

Abstract: Fast and slow decisions exhibit distinct behavioral properties, such as the presence of decision bias in faster but not slower responses. This dichotomy is currently explained by assuming that distinct cognitive processes map to separate brain mechanisms. Here, we suggest an alternative single-process account based on the stochastic properties of decision processes. Our experimental results show perceptual biases in a variety of tasks (specifically: learned priors, tilt aftereffect, and tilt illusion) that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…While in many paradigms such dependencies could in principle arise from changes in early sensory representations, the emerging consensus seems to be that these arise from memory-related processes 17 , 19 . In support of this, recent studies showed that experimental manipulations known to affect memory processes 20 , 21 , such as changing the delay between stimulus and response, alter serial dependencies during judgements of visual orientations 22 , the accumulation of the ventriloquism aftereffect 9 , and longer reaction times reduce perceptual biases in visual discrimination 23 . Collectively, the functional analogy of the trial-wise ventriloquism aftereffect with serial dependencies in perceptual decision making and the neuroimaging studies implying medial parietal regions in the aftereffect, make a strong case for a memory-related component in the trial-by-trial ventriloquism aftereffect.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…While in many paradigms such dependencies could in principle arise from changes in early sensory representations, the emerging consensus seems to be that these arise from memory-related processes 17 , 19 . In support of this, recent studies showed that experimental manipulations known to affect memory processes 20 , 21 , such as changing the delay between stimulus and response, alter serial dependencies during judgements of visual orientations 22 , the accumulation of the ventriloquism aftereffect 9 , and longer reaction times reduce perceptual biases in visual discrimination 23 . Collectively, the functional analogy of the trial-wise ventriloquism aftereffect with serial dependencies in perceptual decision making and the neuroimaging studies implying medial parietal regions in the aftereffect, make a strong case for a memory-related component in the trial-by-trial ventriloquism aftereffect.…”
Section: Introductionmentioning
confidence: 87%
“…orientations 22 , the accumulation of the ventriloquism aftereffect 9 , and longer reaction times reduce perceptual biases in visual discrimination 23 . Collectively, the functional analogy of the trial-wise ventriloquism aftereffect with serial dependencies in perceptual decision making and the neuroimaging studies implying medial parietal regions in the aftereffect, make a strong case for a memory-related component in the trial-by-trial ventriloquism aftereffect.…”
mentioning
confidence: 99%
“…While in many paradigms such dependencies could in principle arise from changes in early sensory representations, the emerging consensus seems to be that these arise from memory-related processes 17,19 . In support of this, recent studies showed that experimental manipulations known to affect memory processes 20,21 , such as changing the delay between stimulus and response, alter serial dependencies during judgements of visual orientations 22 , the accumulation of the ventriloquism aftereffect 9 , and longer reaction times reduce perceptual bias in visual discrimination 23 . Collectively, the functional analogy of the trial-wise ventriloquism aftereffect with serial dependencies in perceptual decision making and the neuroimaging studies implying medial parietal regions in the aftereffect, make a strong case for a memory-related component in the ventriloquism aftereffect.…”
Section: Introductionmentioning
confidence: 88%
“…A second methodological consideration of interest to the current study is response time pressure. Cognitive biases often become stronger when decisions and judgments must be made quickly and under time pressure ( Roberts and Newton, 2001 ; Evans St. and Curtis-Holmes, 2005 ; Hilbig et al, 2012 ; Dekel and Sagi, 2020 ). In previous studies on the negative footprint illusion (e.g., Gorissen and Weijters, 2016 ; Holmgren et al, 2018a , b ), the participants have had essentially as much time as they liked at their disposal to make the estimates.…”
Section: Introductionmentioning
confidence: 99%